Submental Artery Island Flap in Oral Cavity Reconstruction. An Observational, Retrospective Two-centre Study - Ramirez, Adonis Tupac; Chiesa-Estomba, Carlos Miguel; González-García, José Ángel (International Archives of Otorhinolaryngology, 2020)
Introduction The submental flap provides an alternative technique in orofacial reconstruction, especially in situations in which free flaps are not available, or the patients are unfit.Objective To demonstrate the oncological safety and benefits of this flap in oral cavity reconstruction.Methods A total of 14 patients with oral cavity cancers, who underwent submental flap reconstruction from January 2016 to January 2018, were included in the study.Results There were 11 male and 3 female patients with a mean age of 66.7 ± 14 (Min: 52/Max: 91) years old. The most common primary tumor site was the mobile tongue in 12 (85.7%) patients. All of the patients underwent ipsilateral selective neck dissection after the flap was harvested. Flap partial necrosis was observed in one patient, and total necrosis in another one. The mean follow-up was of one year. Nonlocal or regional recurrences were observed.Conclusion Submental island flap represents a good option in oral cavity reconstruction in a restricted setting or in patients considered not fit for free flap reconstruction. Preoperative selection of clinically neck node-negative patients is essential due to the potential risk of occult metastasis.
Keywords: head; neck; oral cavity; reconstruction